Perancangan aplikasi pengukuran tingkat kesiapan inovasi menggunakan user experience lifecycle - Wardhana, Ariq Cahya; Fitriana, Gita Fadila (Universitas Pesantren Tinggi Darul 'Ulum (Unipdu) Jombang, 2021)
Innovation is a process to generate new ideas and change something of value in meeting user needs. Innovation requires measuring the readiness level of innovation in universities to monitor and carry out the resulting innovations. This research was conducted to design an application for measuring the level of innovation using the User Experience Lifecycle (UXL) method. This application can assist in submitting activities and measuring the level of innovation carried out by lecturers or students. This application is made in four stages, namely, analysis, design, prototype, and evaluation. Analysis of user needs is carried out at the Innovation Unit of the Institut Teknologi Telkom Purwokerto through interviews. The interaction design requirements are generated in the form of design requirements and work activity affinity diagrams with two main tasks, namely proposing innovation measurements and obtaining progress reports. After that, a discussion was held in the form of a design thinking and ideation session with the innovation unit that produces personas, sketches, and scenarios. Furthermore, the design implementation is done by creating a medium-fidelity prototype, and the results are tested using the System Usability Scale (SUS). Of the ten questions that must be answered distributed to lecturers and students, the results of the test by the lecturer got a value of 69.17 or B (Good), and students rated 69.40 or B (Good). Based on these results, the application's medium-fidelity prototype has exceeded the minimum requirements of 67 or C (Enough) so that the prototype can be produced so that it can be delivered to the public or the public.